2000
DOI: 10.1002/(sici)1096-9071(200006)61:2<214::aid-jmv7>3.3.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Enterovirus RNA in serum is a risk factor for beta-cell autoimmunity and clinical type 1 diabetes: A prospective study

Abstract: Recent prospective studies have documented serologically an increased frequency of enterovirus infections in prediabetic children, indicating that these infections may initiate and accelerate the beta-cell damaging process several years before the clinical manifestation of type 1 diabetes. The aim of the present study was to establish whether these serological findings would be supported by the detection of enterovirus RNA in a unique prospective series of sera collected from prediabetic children 0-10 years be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
74
1
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(82 citation statements)
references
References 0 publications
5
74
1
2
Order By: Relevance
“…Moreover, infections were also clustered immediately preceding the appearance of autoantibodies even several years before the diagnosis of clinical diabetes [56,57,58,34]. The frequency of other virus infections such as cytomegalovirus, adenovirus and Epstein Barr virus did not differ between the groups [13,56,59].…”
Section: Further Recent Epidemiological Studiesmentioning
confidence: 96%
See 3 more Smart Citations
“…Moreover, infections were also clustered immediately preceding the appearance of autoantibodies even several years before the diagnosis of clinical diabetes [56,57,58,34]. The frequency of other virus infections such as cytomegalovirus, adenovirus and Epstein Barr virus did not differ between the groups [13,56,59].…”
Section: Further Recent Epidemiological Studiesmentioning
confidence: 96%
“…Others have detected enteroviruses by PCR methods in the serum of children genetically at risk for diabetes some months or years before the clinical condition developed [34,35].…”
Section: Coxsackie B Virusesmentioning
confidence: 99%
See 2 more Smart Citations
“…The process, which finally leads to complete beta-cell loss and onset of clinical disease, starts years before any clinical symptoms and is thought to result from several factors involving host genes, autoimmune responses and cytokines, as well as environmental factors. Results from previous cross-sectional and prospective studies on patients with Type 1 diabetes and/or prediabetic individuals have suggested that enterovirus infections are involved in the development of the disease [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15].…”
mentioning
confidence: 99%